2018
DOI: 10.1109/tap.2018.2806421
|View full text |Cite
|
Sign up to set email alerts
|

Low-Cost Ka-band Switchable RHCP/LHCP Antenna Array for Mobile SATCOM Terminal

Abstract: Achieving a functional antenna for mobile SATCOM terminals in Ka band is probably one of the most challenging tasks in current antenna engineering. Even more if this terminal has to exhibit a low profile and be "affordable". This quest is involving many companies in the field. Our contribution represents one of such efforts. The antenna is based on slotted waveguide array technology to maximize efficiency and it features a number of novel solutions, going from its robust polarization switching mechanism, to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 6 publications
0
21
0
Order By: Relevance
“…In large‐scale high gain planar A‐PAA, a few thousand of active antenna elements are employed to provide the required high gain level and to satisfy a certain side lobe level. In practical applications, the antenna array aperture could be one printed circuit board (PCB) standalone panel or divided into two or more separate panels which are still complex and expensive. However, for cost‐effective and less design complexity, smaller active sub‐arrays (modules) with small dimensions, such as 4 × 4 can be used to implement large‐scale A‐PAA aperture in any size (scalable).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In large‐scale high gain planar A‐PAA, a few thousand of active antenna elements are employed to provide the required high gain level and to satisfy a certain side lobe level. In practical applications, the antenna array aperture could be one printed circuit board (PCB) standalone panel or divided into two or more separate panels which are still complex and expensive. However, for cost‐effective and less design complexity, smaller active sub‐arrays (modules) with small dimensions, such as 4 × 4 can be used to implement large‐scale A‐PAA aperture in any size (scalable).…”
Section: Introductionmentioning
confidence: 99%
“…All the RF signals from all the modules are distributed/combined by power splitter/combiner which is integrated at the back‐plane as shown in Figure . Traditionally, power splitters/combiners based metallic planar lines or metallic rectangular waveguide (RWG) are used to split/combine the RF‐power to these modules. However, they are lossy, bulky, or expensive at mm‐wave band.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, GGWs have been successfully utilized in the past for waveguide slot arrays [210]. Also in [208], a study in that sense was carried out. In Fig.…”
Section: Contactless Feature Of Gwmentioning
confidence: 99%
“…The study done in [211] reached the same conclusion. It was shown that the GGW field distribution Figure 2.16: Reflection coefficient comparison for a subarray taken from the antenna presented in [208].…”
Section: Contactless Feature Of Gwmentioning
confidence: 99%